State of Study of Nematofauna of Woody Plants in Uzbekistan (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
This thesis presents an analysis of works devoted to the study of nematoda fauna of woody plants in Uzbekistan. Based on the conducted research, the scientific and practical importance of studying the nematoda fauna of fruit trees in the future has been revealed.Purpose of work. Analyzing the researches devoted to the study of nematodafauna of woody plants in Uzbekistan, thereby revealing the scientific and practical importance of studying the nematodafauna of fruit trees in the futureMaterial and methods. Scientific literature was used in the analysis of studies devoted to the study of the nematoda fauna of woody plants in Uzbekistan.Results. E. P. Azizova's work on the study of the nematode fauna living in the soil around the vine and its root deserves attention in the study of the nematode fauna of shrubs and woody plants in Uzbekistan. The author studied the composition of nematoda fauna of several varieties of vines in the conditions of Tashkent region. As a result of investigations carried out in 1967-1970 in three farms of the Tashkent region, 49 types of soil nematodes belonging to all ecological groups were identified. For the first time in the Republic of Uzbekistan, the species Xiphinema americanum and X. index were detected in the 40 cm depth of the soil around the root of the vine [3].